Various vehicle speeds and road profiles effects on transmitted accelerations analysis to human body segments using vehicle and biomechanical models. Issue 1 (1st January 2018) - Jamali Shakhlavi, Somaye; Marzbanrad, Javad; Tavoosi, Vahid
Abstract: In this paper, a biomechanical model of human body is proposed to evaluate the biodynamic responses to vertical vibration and transmitted accelerations for the seated position without backrest support. Hence, a 6-DoF lumped-parameter model with six concentrated masses, which are connected using several linear springs and dampers, is presented here. Moreover, the full vehicle model is developed in ADAMS/CAR in order to utilize the acceleration of seat under various roads excitation for different amount of vehicle speeds. The transmitted accelerations to the human body segments are evaluated based on applied accelerations under the automotive passenger's seat due to, two various road profiles with two driving cycles. The road profiles consisted of polyline and roughness profiles. Finally, the obtained results illustrated the maximum value of transmitted accelerations for different body segments occurred in frequencies below 5 Hz, it can be concluded that the human body is more sensitive to vibration with frequencies under 5 Hz.